Análise do comportamento do consumidor por meio de estudo de caso - Scassiotti, Ana Paula Ferreira (2010)
The vast majority of studies in the literature on the Consumer Behavior have assumed a method similar to a study design between groups considering a generic/abstract subject. The research objective is to perform an analysis of consumer behavior through the case study. To this end, it was assumed to remain focused on individual consumer behavior (considering an individual as a home), prioritize effectively behavioral information (which records the purchasing behavior and not made reported) and the functional relationships engendered. Then, we examine four households contained in a Consumer Panel provided by the group Latin Panel during each week of 2003, analyzing how buying patterns for four categories of products (laundry detergent, deodorant, cookie and soft drink) took place. Picked up two households in the class AB (one without child and the other with child) and two households in the class DE (also one without child and the other with child). The results showed that the purchasing patterns varied depending on each product, i.e. the purchasing patterns of a family was composed by the conjunction of four different patterns of each product reviewed. For laundry detergent, households without children took an average of 43.61% more than those with children and were the ones who spent a year the highest value in this category. For deodorant, all households had very few episodes of purchase and prioritized products IR type 3. For biscuits, the numbers of households had similar episodes of purchase, bought more items from the UR type 1 and IR type 3. Already, the soft drink product category was the most bought, so when one considers the number of times purchased, as the number of episodes and also the total amount spent. It was seen that the presence of children is a factor that appears to increase the purchase of soft drink by buying opportunity and the total volume purchased. The homes were shown, many times, more faithful to manufacturers than to brands, ranging from marks made by the same manufacturer, mainly products for laundry detergent and deodorant. However, had it been cases, too, especially the cookies that all products purchased from that manufacturer were the same brand. Nevertheless, even in households that were able to identify "preferences" varied between brands within a product category. With this research, we can say that it met most of this method (case study) applied to the Consumer Behavior with an instrument, a Panel of Consumption, than was known before. However, for such a study is detailed, more individual information is required